Farmers’ Perceptions on the Agricultural use of Human Urine in the Central Amazon (2017)
The Urine Diverting Dry Toilet (UDDT) provides a technological alternative for the challenging environments found in Amazonia, and has the advantage of not consuming water. To verify its viability, however, it is necessary to understand user behavior in relation to the use of the toilet’s byproducts. The objective of the present study was to evaluate farmer’s perceptions of the use of human urine as a fertilizer for agricultural crops in the Central Amazon. We interviewed 73 smallholder farmers from a rural village in Tefé County and in the municipal farmers market of Tefé. It was verified that 12% of farmers have knowledge of the use of human urine in agriculture, and that more than a third consider it possible to use urine in their gardens and fields. However, more than half did not consider the possibility of using urine, manifesting concerns about crop development and doubts regarding the efficacy of its use as a fertilizer. The informants believed that crops watered with urine would be adequate for human consumption. It is possible to conclude that human urine has the potential to be used in agriculture in the study region and we understand that dry toilets should not be taken as the only alternative for sanitation in Amazonia.